Effect of Amoxicillin and Clavulanate Potassium Combined with Bazhengsan on Pediatric Urinary Tract Infection. (20th October 2021) - Zhang, Shengjun; Wang, Zhenghua; Xu, Guoping
Abstract : Objective . To explore the therapeutic effect of amoxicillin and clavulanate potassium combined with Bazhengsan on pediatric urinary tract infection (UTI). Methods . The data of 120 UTI children treated in Wuhan Xinzhou District People's Hospital from February 2019 to February 2020 were retrospectively analyzed. They were equally split into experimental group (EG) and control group (CG) according to the order of admission. All children were treated with amoxicillin and clavulanate potassium for suspension (twice a day), and EG was additionally treated with one dose of Bazhengsan daily. Both groups were treated for 10 days. After treatment, the immune function indexes, inflammatory factor levels, and clinical efficacy were compared before and after treatment. Results . No remarkable differences in the general data such as blood routine and urine routine results were observed between the two groups before treatment (P > 0.05 ). After treatment, EG achieved obviously better immune function indexes (P < 0.001 ) and lower levels of inflammatory factors (P < 0.05 ) compared with CG. Besides, the treatment effective rate in EG (96.7%) was higher than that in CG (P < 0.05 ). Conclusion . Amoxicillin and clavulanate potassium combined with Bazhengsan can improve the immune function of UTI children and reduce the levels of inflammatory factors, with remarkable effects, which should be popularized in practice.